Distearoyl Anchor‐Painted Erythrocytes with Prolonged Ligand Retention and Circulation Properties In Vivo. Issue 1 (25th June 2013) - Shi, Guixin; Mukthavaram, Rajesh; Kesari, Santosh; Simberg, Dmitri
Abstract Red blood cells (RBCs) attract significant interest as carriers of biomolecules, drugs, and nanoparticles. In this regard, versatile technologies to attach molecules and ligands to the RBC surface are of great importance. Reported here is a fast and efficient surface painting strategy to attach ligands to the surface of RBCs, and the factors that control the stability and circulation properties of the modified RBCs in vivo. Distearoyl phosphatidylethanolamine anchor‐conjugated immunoglobulin (IgG) efficiently incorporates in the RBC membrane following 15–30 min incubation. The optimized RBCs show prolonged circulation in vivo (70% of the injected dose after 48 h) and efficient retention of IgG in the membrane with terminal half‐life of 73 h. The IgG construct is gradually lost from the RBCs mainly due to the transfer to plasma components, liver endothelial cells, and Kupffer cells. The ligand retention efficiency is partially dictated by ligand type, anchor type, and ligand concentration in the membrane, while RBC half‐life is determined by initial concentration of the ligand in the membrane and presence of PEG linker between the ligand and the anchor. This work provides important guidance for non‐covalent surface painting of RBCs as well as other types of blood borne cells for in vivo therapeutic and targeting applications.